IDH-mutant glioma risk stratification via whole slide images: Identifying pathological feature associations - Xiaotao Wang; Zilong Wang; Weiwei Wang; Zaoqu Liu; Zeyu Ma; Yang Guo; Dingyuan Su; Qiuchang Sun; Dongling Pei; Wenchao Duan; Yuning Qiu; Minkai Wang; et al. (iScience)
Summary: This article aims to develop and validate a pathological prognostic model for predicting prognosis in patients with isocitrate dehydrogenase (IDH)-mutant gliomas and reveal the biological underpinning of the prognostic pathological features. The pathomic model was constructed based on whole slide images (WSIs) from a training set (N = 486) and evaluated on internal validation set (N = 209), HPPH validation set (N = 54), and TCGA validation set (N = 352). Biological implications of PathScore and individual pathomic features were identified by pathogenomics set (N = 100). The WSI-based pathological signature was an independent prognostic factor. Incorporating the pathological features into a clinical model resulted in a pathological-clinical model that predicted survival better than either the pathological model or clinical model alone. Ten categories of pathways (metabolism, proliferation, immunity, DNA damage response, disease, migrate, protein modification, synapse, transcription and translation, and complex cellular functions) were significantly correlated with the WSI-based pathological features.